Effect of low plastic tunnels, transplanting dates and mulching on quality of tomato (Solanum lycopersicum) - DUHAN, ANSUL; SINGH, DAVINDER; KUMAR, AMIT; MAAN, DEVA SHRI (The Indian Journal of Agricultural Sciences, 2021)
The present experiment was conducted at Research Farm and in Laboratory of the CCS Haryana AgriculturalUniversity, Hisar during spring summer 2014–15 and 2015–16 to study the influence of low plastic tunnels, transplanting dates and mulching on quality characteristics of tomato (Solanum lycopersicum L.). The treatments comprise two types tunnels, three transplanting dates and three types mulching materials which were laid out in factorial RBD design with three replications. Results of the study showed that pericarp thickness (3.02 mm), acidity (0.48%), ascorbic acid (26.61 mg/100 g) and TSS (5.68%) content in tomato fruits were recorded significantly higher when seedlings were transplanted under low plastic tunnel on 30 November using black polyethylene as mulch materials compared to other treatments. Moreover fruit firmness (4.66 kg/cm) was recorded significantly higher value when seedlings were transplanted under plastic low tunnel on 20 December with black polyethylene mulch during both the years.